2022
DOI: 10.1136/bmjopen-2021-060730
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of diabetes mellitus in the Chinese population: a dynamic cohort study

Abstract: ObjectiveDiabetes mellitus is a common condition often associated with an ageing population. However, only few longitudinal studies in China have investigated the incidence of diabetes and identified its risk factors. Therefore, this study aimed to investigate the incidence and risk factors of diabetes in Chinese people aged ≥45 years using the harmonised China Health and Retirement Longitudinal Study (CHARLS) data.DesignA dynamic cohort study.SettingThe harmonised CHARLS 2011–2018.Participants19 988 adults ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“… 60 Xue et al found that alcohol consumption is associated with an increased risk of DM. 53 This study showed no clear correlation between the incidence of DM and smoking or alcohol consumption in HTN patients. 60 In this study, there was no significant relationship between smoking and alcohol consumption and the risk of DM in HTN patients, which may be related to the differences in research methods, study sample size, and indicators included in the analysis of different studies, which need to be confirmed by further research.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“… 60 Xue et al found that alcohol consumption is associated with an increased risk of DM. 53 This study showed no clear correlation between the incidence of DM and smoking or alcohol consumption in HTN patients. 60 In this study, there was no significant relationship between smoking and alcohol consumption and the risk of DM in HTN patients, which may be related to the differences in research methods, study sample size, and indicators included in the analysis of different studies, which need to be confirmed by further research.…”
Section: Discussioncontrasting
confidence: 55%
“… 51 , 52 Xue et al found that age is associated with an increased risk of DM. 53 However, study has reported inconsistent results. 54 This study showed that the incidence of DM in different age groups was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of diabetes is growing every year. The occurrence rate of T2DM in China was at 12.4% in 2018, and its complications have become a significant burden on the health of Chinese people (Xue et al, 2022). Patients diagnosed type 1 diabetes mellitus (T1DM) need to inject insulin daily to control their blood glucose.…”
Section: Introductionmentioning
confidence: 99%